Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1177/0885066617714209
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of Vasopressin Before Norepinephrine in the Recovery Phase of Septic Shock

Abstract: Adult patients receiving norepinephrine and vasopressin in the resolving phase of septic shock may be less likely to develop clinically significant hypotension if vasopressin is the final vasopressor discontinued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 27 publications
(54 reference statements)
1
57
1
Order By: Relevance
“…9-11,21,24,28,30 Additional areas with unclear clinical data where cost savings could be realized include initiating vasopressin at a dosage of 0.03 units/min (as opposed to 0.04 units/min) and discontinuing vasopressin prior to norepinephrine. [12][13][14][15][16]31 Although vasopressin up to 0.06 units/min has been used with minimal safety concerns, 24 the seminal trial used 0.03 units/min, 26 which is the guideline-recommended dosage. 1 Evaluations of adjuvant vasopressor strategies for patients in whom norepinephrine monotherapy is inadequate, the discontinuation order of vasoactive medications, and the Those surveyed were asked to indicate their agreement or disagreement with the use of vasopressin for the listed indications for patients with septic shock while considering both available evidence for treatment and cost and while just considering the available evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9-11,21,24,28,30 Additional areas with unclear clinical data where cost savings could be realized include initiating vasopressin at a dosage of 0.03 units/min (as opposed to 0.04 units/min) and discontinuing vasopressin prior to norepinephrine. [12][13][14][15][16]31 Although vasopressin up to 0.06 units/min has been used with minimal safety concerns, 24 the seminal trial used 0.03 units/min, 26 which is the guideline-recommended dosage. 1 Evaluations of adjuvant vasopressor strategies for patients in whom norepinephrine monotherapy is inadequate, the discontinuation order of vasoactive medications, and the Those surveyed were asked to indicate their agreement or disagreement with the use of vasopressin for the listed indications for patients with septic shock while considering both available evidence for treatment and cost and while just considering the available evidence.…”
Section: Discussionmentioning
confidence: 99%
“…8 Other initiatives to identify optimal strategies for vasopressin use in septic shock that were evaluated for effects on clinical outcomes have included restriction of vasopressin use in septic shock until the norepinephrine infusion rate is above 50 mcg/min; 9 early, concomitant initiation of norepinephrine and vasopressin; 10,11 and the order of vasopressin discontinuation in resolving septic shock. [12][13][14][15][16] Many of these studies evaluated a small number of clinicians/institutions and failed to evaluate some of the clinical scenarios where vasopressin is often used (eg, severe acidemia, elevated lactate).…”
Section: Introductionmentioning
confidence: 99%
“…However, this 4‐hour requirement for maintenance of MAP is more likely to reflect the true transition point from early septic shock to the maintenance phase of septic shock than previously studied 1‐hour requirements for maintaining target MAP. More patients in the early concomitant vasopressin and norepinephrine group had vasopressin discontinued before norepinephrine in the resolving phase of septic shock that would not have any bearing on time to achieving and maintaining target MAP but may have affected duration of both vasopressors and intensive care unit length of stay . Finally, vasopressin was provided at an initial rate of 0.04 units/minute.…”
Section: Discussionmentioning
confidence: 99%
“…More patients in the early concomitant vasopressin and norepinephrine group had vasopressin discontinued before norepinephrine in the resolving phase of septic shock that would not have any bearing on time to achieving and maintaining target MAP but may have affected duration of both vasopressors and intensive care unit length of stay. [24][25] Finally, vasopressin was provided at an initial rate of 0.04 units/minute. The most recent iteration of the Surviving Sepsis Campaign guidelines recommends an initial rate of 0.03 units/minute.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a higher incidence of hypotension after vasopressin discontinuation compared with NE discontinuation. [29][30][31][32][33] Patient demographics, vasopressor utilization, and clinical outcomes were similar to the overall cohort (Tables S1 and S2, Supporting Information).…”
Section: Discussionmentioning
confidence: 71%